EXPERIMENTAL EVIDENCE FOR CARBONATE PRECIPITATION AND CO2 DEGASSING DURING SEA ICE FORMATION - Papadimitriou S.; Kennedy H.; Kattner G.; Dieckmann G.S.; Thomas D.N. (My University, 2004)
Chemical and stable carbon isotopic modifications during the freezing of artificial seawater were measured in four 4 m3 tank incubations. Three of the four incubations were inoculated with a nonaxenic Antarctic diatom culture. The 18 days of freezing resulted in 25 to 27 cm thick ice sheets overlying the residual seawater. The ice phase was characterized by a decrease in temperature from −1.9 to −2.2°C in the under-ice seawater down to −6.7°C in the upper 4 cm of the ice sheet, with a concurrent increase in the salinity of the under-ice seawater and brine inclusions of the ice sheet as a result of physical concentration of major dissolved salts by expulsion from the solid ice matrix. Measurements of pH, total dissolved inorganic carbon (CT) and its stable isotopic composition (δ13CT) all exhibited changes, which suggest minimal effect by biological activity during the experiment. A systematic drop in pH and salinity-normalized CT by up to 0.37 pHSWS units and 376 μmol C kg−1 respectively at the lowest temperature and highest salinity part of the ice sheet were coupled with an equally systematic 13C enrichment of the CT. Calculations based on the direct pH and CT measurements indicated a steady increase in the in situ concentration of dissolved carbon dioxide (CO2(aq)) with time and increasing salinity within the ice sheet, partly due to changes in the dissociation constants of carbonic acid in the low temperature-high salinity range within sea ice. The combined effects of temperature and salinity on the solubility of CO2 over the range of conditions encountered during this study was a slight net decrease in the equilibrium CO2(aq) concentration as a result of the salting-out overriding the increase in solubility with decreasing temperature. Hence, the increase in the in situ CO2(aq) concentration lead to saturation or supersaturation of the brine inclusions in the ice sheet with respect to atmospheric pCO2 (≈3.5 × 10−4 atm). When all physico-chemical processes are considered, we expect CO2 degassing and carbonate mineral precipitation from the brine inclusions of the ice sheet, which were saturated or highly supersaturated with respect to both the anhydrous (calcite, aragonite, vaterite) and hydrated (ikaite) carbonate minerals.